2017
DOI: 10.1016/j.yexcr.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Septin 7 reduces nonmuscle myosin IIA activity in the SNAP23 complex and hinders GLUT4 storage vesicle docking and fusion

Abstract: Glomerular epithelial cells, podocytes, are insulin responsive and can develop insulin resistance. Here, we demonstrate that the small GTPase septin 7 forms a complex with nonmuscle myosin heavy chain IIA (NMHC-IIA; encoded by MYH9), a component of the nonmuscle myosin IIA (NM-IIA) hexameric complex. We observed that knockdown of NMHC-IIA decreases insulin-stimulated glucose uptake into podocytes. Both septin 7 and NM-IIA associate with SNAP23, a SNARE protein involved in GLUT4 storage vesicle (GSV) docking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 55 publications
1
38
0
Order By: Relevance
“…Wild‐type mouse podocytes and podocytes stably over‐expressing nephrin were produced and maintained as described in Wasik et al (16). Sodium palmitate (Sigma‐Aldrich, St. Louis, MO, USA) was conjugated to free fatty acid‐free bovine serum albumin (BSA) (Sigma‐Aldrich) at a 3:1 molar ratio at 37°C for 1–2 h. When specified, medium was supplemented with 50 μM BSA‐palmitate, and/or glucose concentration was increased from 25 to 40 mM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild‐type mouse podocytes and podocytes stably over‐expressing nephrin were produced and maintained as described in Wasik et al (16). Sodium palmitate (Sigma‐Aldrich, St. Louis, MO, USA) was conjugated to free fatty acid‐free bovine serum albumin (BSA) (Sigma‐Aldrich) at a 3:1 molar ratio at 37°C for 1–2 h. When specified, medium was supplemented with 50 μM BSA‐palmitate, and/or glucose concentration was increased from 25 to 40 mM.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoperoxidase staining was performed as described in Wasik et al (16), with an additional incubation at room temperature for 1 h prior to incubation over night at +4°C with anti‐PACSIN2 IgG (P2P). Images of 15–24 glomeruli per rat ( n = 6–8 per group) were taken by a researcher blinded to phenotype.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetic nephropathy (DN) is the most common cause of end-stage renal disease worldwide, mainly characterized by extra-cellular matrix (ECM) accumulation, glomerular basement membrane (GBM) thickening and podocyte injury [1-3]. ECM accumulation and GBM thickening used to be considered as the primarily important mechanisms in the pathogenesis of DN.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SEPT7 also binds to the t-SNARE SNAP23 suggesting that SEPT7 could be involved in the regulation of the GSV docking process (Wasik et al, 2012). In line with this, SEPT7 was found to form a complex with nonmuscle myosin heavy chain IIA (NMHC-IIA; encoded by MYH9; Wasik et al, 2017), which has been shown to regulate glucose uptake in adipocytes by influencing the docking and fusion of GSVs as well as the activity of GLUT4 (Steimle, Fulcher, & Patel, 2005). …”
Section: Regulation Of Cell Motilitymentioning
confidence: 75%